PENGARUH KUALITAS PELAYANAN DI DIVISI CUSTOMER SERVICE TERHADAP PENCITRAAN BANK PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK.KANTOR CABANG CIMAHI - Yuyun Arlian, - (2012)
Focus discussing on this research is the existing of bank's image the prediction happen because of the quality of good service in Customer Service Division that haven't optimal in PT. BRI (Persero) bank, Tbk, The Branch Office Of Cimahi. That problem is solved by three regular questions by finding the future of good service in Customer Service Division, the future of the quality of bank's image and how big the influence of service quality in Customer Service Division to the image of PT. Bank Rakyat Indonesia (persero), Tbk, The Branch Office Of Cimahi. The result of analysis from respondent file is gotten that X variable is the quality of good service in Customer Service Division in PT. BRI (Persero), Tbk, The Branch Office Of Cimahi include the high category, and Y variable is the image of PT. BRI (Persero) bank, Tbk, The Branch Of Cimahi include in high category too. Based on the simple calculating regression coefficient, is getting the result of supported suggestions hypothesis that the quality of good service in Customer Service Division has positive influence and significantly to bank's image. Futhermore, from several indicators that has been examining in this research there is still indicator that have been lower identify which is the lower indicator emphaty to the variable quality of service low, and the lower indicator reputation to the image variable bank. So that's why PT BRI (persero), Tbk. The Branch Office Of Cimahi is suggested to increase the quality indicators quality in order to PT. BRI (Persero), Tbk The Branch Office Of Cimahi is better in the next future.